Changes in the prevalence of obesity in Czech adolescents between 2018 and 2022 and its current non-genetic correlates - HBSC study - Erik Sigmund; Dagmar Sigmundová; Jan Pavelka; Michal Kalman; Jaroslava Voráčová; Zdeněk Meier; Jaroslava Kopčáková; Petr Badura (BMC, 2023)
Abstract Background The main aim of the study is to examine changes in the prevalence of obesity in Czech adolescents between 2018 and 2022 and its current non-genetic correlates with respect to the adolescents' families'socioeconomic status (SES) in 2022. Methods The sample of 24,535 adolescents (n = 11,629/12,9062018/2022; boys: 50.4/50.6%2018/2022) aged 10.5-16.5 years that was analysed was drawn from two nationally representative cohorts of Czech youngsters from the last two cycles of the Health Behaviour in School-aged Children (HBSC) online questionnaire survey from 2018 to 2022. Obesity is represented by the > 97th percentile interval on the World Health Organization Body Mass Index percentile chart, with distinctions by sex and the age of adolescents. The differences in the prevalence of obesity between boys and girls from all SES family categories in 2018 and 2022 were tested using a chi-square test (χ 2). Multiple logistic regression analysis with repeated measures was used to analyse correlates of obesity in 2022. Results Between 2018 and 2022, there was no significant difference in the prevalence of obesity in girls or boys in any of the SES categories of families. Adolescents from low-SES families have the highest prevalence of obesity, 11% for boys and 5.8% for girls, significantly higher (p < .001) than its prevalence among adolescents from high-SES families, by + 4.8% points for boys and + 3.9% points for girls. Among adolescents from low-SES families, individuals who engaged in moderate-to-vigorous physical activity (PA) daily (p < .005) or vigorous PA three times per week (p < .05) were significantly less likely to be obese than their less active peers. Skipping breakfast significantly (p < .05) increased the odds of obesity, but only among adolescents from low-SES families. Shorter screen time (ST) significantly (p < .05) reduced the odds of obesity for all categories of adolescent SES. Conclusions Obesity is most pronounced in adolescents from low-SES families as a result of a long-term positive energy balance mediated by unbalanced behaviour. Significantly lower odds of obesity in adolescents from low-SES families were confirmed to be associated with regular practice of the recommended PA, shorter ST, and not skipping breakfast.